Identificação de condições eficientes no ensino de discriminações para bebês com até 21 meses - Sousa, Naiara Minto de (2009)
One of the most complex human abilities is the symbolic thought that is related to the acquisition of arbitrary relational repertoires such as conditional discrimination. However, research on the acquisition of these repertoires in babies up to 24 months was hampered by methodological difficulties. The literature has identified some critical variables for the maintenance of these participants in experimental situation and other variables related to the process of learning the tasks by the babies. This research investigated procedures for teaching simple and conditional visual discrimination in infants aged 15 to 21 months. In the first part of the investigation - Study 1 - the tasks proposed to the participants were simple simultaneous discrimination and delayed identity conditional discrimination. Various industrialized toys had different functions as stimulus and were exposed in a motorized apparatus specially built for the study. The first study evaluated the effects of variation of the order and amount of exposure of participants to differential reinforcement contingencies on the performance of babies in simple discrimination tasks. In Study 2, simple simultaneous discrimination tasks, discrimination reversal and delayed arbitrary conditional discrimination tasks have been proposed to the participants in a play context where some photographs of animals were exposed in a bound book of paper card. This study evaluated the effects of the requirement of observational and choice responses similar to those issued in natural situation of free play between adults and babies. The investigation has identified effective conditions of teaching in two aspects - achievement of the learning criteria of discrimination tasks by participants and for their permanence in the experimental situation over the experimental procedures, respectively: 1) the procedure of contact with differential reinforcement contingencies that occurred in more trials and planned the positive reinforcement (S+) to occur in the first trial; 2) the procedure of requirement of observational and choice responses present in the baby repertoire and the experimental arrange of the effective reinforcer stimuli as part of the task (exerting function of reinforcer or sample stimulus). The general discussion stressed the importance of knowledge by researchers from the expected repertoire of participants in a specific age for planning tasks and requiring responses closer form that naturally emitted in babies daily activities. Likewise, researchers must know the individual repertoire of each baby so they can arrange the effective reinforcer stimulus for each participant.